2009
DOI: 10.1063/1.3240891
|View full text |Cite
|
Sign up to set email alerts
|

Strain-relief pattern as guide for the formation of surface-supported bimolecular nanoribbons

Abstract: We demonstrate the suitability of the Ag/Pt͑111͒ strain-relief pattern as efficient template for controlling the formation of well defined heteromolecular nanostructures. Two different species of molecular building blocks with complementary end-group functionalities are combined on this surface, which results in the formation of robust bimolecular nanoribbons driven by the interplay of the site specific adsorption on the strain-relief pattern with the highly directional intermolecular hydrogen-bonding intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Lattice strain is justified by the significantly different atomic sizes of RE and NM atoms. Achieving active control of these competing processes offers great potential to design moiré patterns with complex spin-dependent band structures and hence to template nanostructures for site-specific absorption of (organic) adsorbate, or the formation of heteromolecular nanostructures [53].…”
Section: Discussionmentioning
confidence: 99%
“…Lattice strain is justified by the significantly different atomic sizes of RE and NM atoms. Achieving active control of these competing processes offers great potential to design moiré patterns with complex spin-dependent band structures and hence to template nanostructures for site-specific absorption of (organic) adsorbate, or the formation of heteromolecular nanostructures [53].…”
Section: Discussionmentioning
confidence: 99%
“…This study was also extended to another template surface, the strain-relieved pattern formed by two monolayers of Ag on Pt (111). 306 It was shown that this template could also be used to control the orientation of the H-bonded rows by strong molecular pinning on the pattern.…”
Section: Chemical Reviewsmentioning
confidence: 97%
“…303 It was shown that this template could also be used to control the orientation of the H-bonded rows by strong molecular pinning on the pattern.…”
Section: Figure 11 Mono-and Bicomponent Self-assembly Of Bdatb 6-phmentioning
confidence: 99%
“…5,6 Nevertheless, the TN exhibits remarkable template functions. Well-ordered sputter holes 5 and adsorbed organic molecules, [6][7][8] as well as strong spatial variations of the local work function 9 have been reported. A fundamental understanding of any template function evidently requires knowledge of its atomic structure.…”
mentioning
confidence: 97%